Ediçao de textos publicitários na tela do computador : da apropiaçao pelos professores á prática na sala de aula - Figueredo, Angela Maria da Silva (2017)
This investigation identifies, caracterizes and analyses activities, arguments and acquirements that present teachers of the 2nd, 3rd, 4th and 5th grades of the elementary school, - who took part of the program "Ler e Escrever" (Read and Write), offered by the State Education Network, in Sao Paulo, Brazil - on contents involved in a sequence of activities that proposed to teachers to put themselves in the role of publishers of advertising texts on the computer screen (own knowledge), to elaborate a didactical situation from that experience (to turn their own knowledge into didactical knowledge - a didactical transposition) and to develop the activity in the classroom (a didactical operation). The first two steps were developed with teachers working in pairs. The literacy conception that grounds this research is "alfabetizaçao simplesmente. A que corresponde ao nosso espaço e tempo" (simply literacy. The one that corresponds to our space and time) (Ferreiro, 2013, pp. 468-469), and, for that reason, it involves social practices of reading and writing, which, nowadays, are permeated by the massive progress of Information and Comunication Technologies. The hypothesis that guides this analysis is that the teachers who were involved - the ones who took part of the program "Ler e Escrever" (Read and Write) - transpose the principles that were built in the process of education by planning and developing a didactical situation that involves a content that was not intentionally approached with them in educational situations. This exploratory-descriptive and transverse study analyzed and interpreted questions proposed through a qualitative approach of data which led to the construction of categories that were also qualitative. This investigation deals with the history of text publishing in the core of the writing culture expressed in social and didactical practices and, also, the didactical and psycholinguistic investigations on a Constructivist basis.